Effects of 6% hydroxyethyl starch 130/0.4 on postoperative blood loss and kidney injury in off-pump coronary arterial bypass grafting: A retrospective study. Issue 18 (May 2017) - Min, Jeong Jin; Cho, Hyun Sung; Jeon, Suyong; Lee, Jong-Hwan; Lee, Jeong Jin; Lee, Young Tak
Abstract : Abstract: We retrospectively evaluated the effects of 6% hydroxyethyl starch (HES) 130/0.4 on postoperative blood loss and acute kidney injury (AKI) in patients undergoing off-pump coronary artery bypass grafting (OPCAB). Electronic medical records of 771 patients who underwent OPCAB in our hospital between July 2012 and July 2014 were reviewed, and 249 patients without intraoperative HES-exposure (group NoHES) were matched 1:N with intraoperative HES-exposed 413 patients (group HES) based on propensity score. The effects of intraoperative HES on postoperative cumulative blood loss within the first 24 hours, need for bleeding-related reoperation, and occurrence of postoperative AKI (determined by KDIGO and RIFLE criteria) were analyzed. In our propensity score matched cohort, there were no significant differences between groups for median postoperative 24 hours blood loss (525 mL in group HES vs. 540 mL in group NoHES, P = .203) or need for bleeding-related reoperation (OR, 2.44; 95% confidence interval [CI], 0.64–9.34, P = .19). However, postoperative AKI (assessed by 2 criteria) occurred more frequently in group HES than in group NoHES (by KDIGO criteria: 10.7% vs. 3.6%; OR 3.43 [95% CI, 1.67–7.04]; P < .001 and by RIFLE criteria: 9.6% vs. 2%; OR 3.32 [95% CI, 1.34–8.24]; P = .01). The median volume of infused HES per patient weight was 16 mL/kg in group HES. In the patients undergoing OPCAB, intraoperative 6% HES 130/0.4 did not increase postoperative bleeding. However, renal safety remains a concern. Intraoperative use of HES should be determined cautiously during OPCAB.